2015
DOI: 10.1037/xlm0000126
|View full text |Cite
|
Sign up to set email alerts
|

Studying on borrowed time: How does testing impair new learning?

Abstract: Retrieving studied materials often enhances subsequent learning of new materials (Pastötter & Bäuml, 2014). However, retrieval has also been shown to impair new learning (Finn & Roediger, 2013). Here we attempted to determine when retrieval enhances and when it impairs new learning. We argue that testing impairs new learning when one intermixes testing with new learning, which biases participants to relearn the tested information at the expense of the new information. We refer to this as the borrowed time hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 51 publications
2
35
0
Order By: Relevance
“…Of most relevance to the present study, retrieval can enhance new learning by reducing inattention globally (Past€ otter, Schicker, Niedernhuber, & Bauml, 2011;Szpunar, Khan, & Schacter, 2013), such that children who had received an earlier interview were more likely to sustain their attention during the post-event narrative. Further, the initial interview may enhance learning of the post-event information by making encoding more selective (Carpenter & Toftness, 2017;Davis & Chan, 2015). In the context of RES, the children who have received the initial interview may be more likely to detect conflicts between their recollection and the post-event information, thereby enhancing their learning towards the misinformation (Butler & Loftus, 2017;Gordon & Thomas, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Of most relevance to the present study, retrieval can enhance new learning by reducing inattention globally (Past€ otter, Schicker, Niedernhuber, & Bauml, 2011;Szpunar, Khan, & Schacter, 2013), such that children who had received an earlier interview were more likely to sustain their attention during the post-event narrative. Further, the initial interview may enhance learning of the post-event information by making encoding more selective (Carpenter & Toftness, 2017;Davis & Chan, 2015). In the context of RES, the children who have received the initial interview may be more likely to detect conflicts between their recollection and the post-event information, thereby enhancing their learning towards the misinformation (Butler & Loftus, 2017;Gordon & Thomas, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that, when the tested and new materials are presented together, the tested materials may “forcibly occupy” the encoding time and borrow the limited time available for studying new materials––the borrowed time effect . 51…”
Section: Possible Negative Effects Of Interim Testingmentioning
confidence: 99%
“…A substantial literature has shown that performing retrieval practice can strengthen learning of subsequent material, even if that subsequent material is unrelated to the tested, previously learned material [1921]. This more general TPL effect has been ascribed to the ability for retrieval to reduce proactive interference from prior learning [22], reduce mind wandering [23], promote a mental context shift [24,25], and optimize one’s encoding strategies [6,26,27]. For present purposes, regardless of the exact mechanisms (i.e., specific or general) by which testing potentiates subsequent learning, the TPL account places a heavy emphasis on the enhanced encoding of misinformation as the key contributor to RES.…”
Section: Introductionmentioning
confidence: 99%